Changes in suicide mortality trends in Chile, 1997-2018 - Carolina Vidal; Carlos Faunes; Carol Toro Huerta; Cristóbal Ruiz-Tagle; Lorena Hoffmeister (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Using information from the mortality database at Chile's Department of Statistics and Health Information (Ministry of Health), an ecological time-series study was conducted to determine changing trends in suicide rates by sex and age group in Chile from 1997 to 2018. Results show that the mortality rate for men in 2018 was 20.1 per 100,000, almost five times higher than the rate for women. Trends in both sexes show a decrease in aver-age annual percent change of -5.4% [CI95% (-12.9; 1.9)] between 2009 and 2013. Over the same period, the average annual percent change for men was -5.8% [CI95% (-12.5; 2.3)], while for women it was -4.0 [CI95% (-5.8; -2.2)] between 2008 and 2018. No changes have been observed in trends for men aged 60 and over, the group with the high-est rates. Although suicide rates declined following the implementation of policies focus-ing on risk factors for suicide, it is necessary to evaluate the implementation of these pol-icies and devise similar actions geared toward populations with greater risk of suicide.